OLEOGELS – AN ALTERNATIVE TO REPLACE ANIMAL FATS IN MEAT PRODUCTS - Tanja Stojanovska (Journal of Agriculture and Plant Sciences, 2024)
The changes in lifestyle of modern consumers have increased demand for healthier meat products. Animal fat, which is an integral part of meat products, is directly related to the occurrence of chronic diseases and overweight. Polyunsaturated vegetable oils are healthier for human consumption, but their liquid consistency can pose a problem when directly applied in the technological process. Application of oleogels, obtained with innovative technology for gelling vegetable oils using gelators, is a new approach to create healthier meat products with an improved fatty acid profile. This paper aims to review the different approaches for obtaining oleogels and the latest trends for their use in meat products.